TINJAUAN KELENGKAPAN PENGISIAN FORMULIR RESUME MEDIS PADA DOKUMEN REKAM MEDIS RAWAT JALAN DI RSUD CIKALONGWETAN - Hada, Encep; Monica, Rizqi Dimas; Sari, Rani Permata (Jurnal TEDC; Vol 19 No 1 (2025): JURNAL TEDCDO - 10.70428/tedc.v19i1.1207, 2025)
Based on the results of a preliminary study conducted by the author in July 2024 at Cikalongwetan Regional Hospital, from 50 outpatient medical record files, the author analyzed the medical resume forms in the medical record documents and found that 50 files or 100% of the medical resume forms were not filled in completely. This study aims to determine the effect of the completeness of outpatient medical resumes on the quality of medical records at Cikalongwetan Regional Hospital. The research method used by the author is qualitative research. The results of the research show that the implementation of filling out patient medical resumes at Cikalongwetan Regional Hospital has not been carried out according to the regulations by the relevant officers because there is no SOP (Standard Operational Procedure) which regulates filling out and also the flow of medical resumes so that The patient's medical resume is not filled in 100%. Parts of the form that are not filled in completely include the person in charge, discharge date, admission diagnosis, main diagnosis, diagnosis code, doctor's name, doctor's signature, conditions at the time of discharge and how to go home. The author suggests that it is best to create an SOP regarding the implementation of filling out medical resumes, conducting outreach to DPJP to fill in diagnoses, and actions on patient medical resumes.